Truth Of Scientific Philosophy Perspectives In The Development Of The Islamic Economy In The Age Of Globalization - Udin, Ahmad Faqih; Yahya, Muchlis; Marjuni, Kamaluddin Nurdin (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
The philosophy of philanthropy has a major impact on the development of the Islamic economy in the modern era of globalization. This research method is qualitative library using a narrative approach. As for data collection techniques, it's orientation and exploration. The result of this research is that the truth of truth can be used as a concrete or abstract word. If the subject wants to tell the truth, it means that the proposition is true. Then there are the theories of the truths of philosophy, namely the theory of coherence, performative theory, consensus theory and correspondence theory. The truth has two main roles in the development of the Islamic economy. First, to formulate and conceive a new Islamic economic theory. Second, to test and evaluate the Islamic economy theory empirically.